2018
DOI: 10.1002/pon.4733
|View full text |Cite
|
Sign up to set email alerts
|

Maternal perceptions of BRCA genetic counseling communication processes about disclosing cancer risk information to children and adult relatives

Abstract: When the assessment of BRCA genetic counseling outcomes includes family communication to potentially at-risk relatives, we learned that most but not all sessions addressed this topic. Cancer family history, child age, and maternal attitudes are important co-factors in these patient-provider communication exchanges. Providers delivering BRCA genetic counseling should be attentive to mothers' information and support needs regarding communicating cancer genetic test results to at-risk relatives, including childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Once an individual is identified to have a mutation in a high‐penetrance inherited cancer predisposition gene, it becomes very important that this information be shared with at‐risk relatives so that they too can be proactive with cancer risk management (especially if they are confirmed to have the identified familial mutation) 14 . Most HBC syndromes are inherited in an autosomal dominant pattern, meaning that first‐ and second‐degree relatives of a known mutation carrier have a 50% and 25% chance, respectively, to also carry the mutation 46,47 . The first individual within a family found to harbor a mutation is generally responsible for sharing their positive result with relatives.…”
Section: Improving Identification Of Hereditary Cancer Predispositionmentioning
confidence: 99%
“…Once an individual is identified to have a mutation in a high‐penetrance inherited cancer predisposition gene, it becomes very important that this information be shared with at‐risk relatives so that they too can be proactive with cancer risk management (especially if they are confirmed to have the identified familial mutation) 14 . Most HBC syndromes are inherited in an autosomal dominant pattern, meaning that first‐ and second‐degree relatives of a known mutation carrier have a 50% and 25% chance, respectively, to also carry the mutation 46,47 . The first individual within a family found to harbor a mutation is generally responsible for sharing their positive result with relatives.…”
Section: Improving Identification Of Hereditary Cancer Predispositionmentioning
confidence: 99%
“…Participants' knowledge of key genetic health concepts was assessed using a measure containing 14 true/false items. The measure was taken from a 16‐item true/false scale utilized in a previous study on parental genetic testing for cancer risk (Hamilton et al, 2018). In the present sample, internal consistency of the measure was excellent (KR‐20 = 0.90) and 53% of parents scored at or above 80% correct.…”
Section: Methodsmentioning
confidence: 99%
“…The 92 participants had 417 living FDRs. Mean family size was 4.5 ± 2.06 (range, [1][2][3][4][5][6][7][8][9][10][11]. The correlation between family size and the proportion of relatives who were told about their risk was not statistically significant (r = −0.096, P = .362).…”
Section: Relationship Characteristics Of Probands With Their Fdrsmentioning
confidence: 99%
“…The genetic risk communication from proband to relatives varies from family to family, and patients and their families often need support with the communication of genetic test results, coping, and making decisions to manage hereditary cancer risks effectively 9 . For probands, the genetic counseling process should focus on understanding genetic risks of family members and the importance of communicating the risk so that family members may benefit from testing and subsequent risk reduction strategies 10–13 . Despite the critical need to support family communication of genetic risks, Hamilton et al 11 reported that family communication is not consistently included as part of a genetic counseling session.…”
mentioning
confidence: 99%
See 1 more Smart Citation